ALLERGIC RHINITIS: DIAGNOSTICS AND TREATMENT (BASED ON EDUCATIONAL PROGRAM FOR PEDIATRICIANS) - A.K. Gevorkyan; A.Yu. Tomilova; L.S. Namazova; V.V. Botvin'eva (Union of pediatricians of Russia, 2008)
In the presented materials, the authors present one of the most widespread allergic diseases in children - allergic rhinitis, its classification, clinical implications, diagnostic techniques. The principles of treatment for this pathology are examined in more detail, with consideration of improvements in the pharmacology and newly appeared medications prophylactic measures against allergic rhinitis are given.Key words: allergic rhinitis, prevalence rate, clinical treatment, diagnostics, treatment, prophylaxis, children.